Pengaruh Kepercayaan pada Pemerintah dan Persepsi Keadilan Pajak Terhadap Kepatuhan Pajak - Monica Fitrianedi Jamel; Charoline Cheisviyanny (Universitas Negeri Padang, 2024)
The main objective of this research is to determine how tax compliance is influenced by factors such as trust in government and perceptions of tax fairness. This research relies on data obtained from answers to questionnaire statements given to respondents. This research uses a probability sampling method involving 100 non-employee individual taxpayers registered with KPP Pratama Padang City. To test the hypothesis, this research uses path analysis. Research findings show that trust in government and perceptions of tax fairness can mediate the relationship between trust in government and tax compliance.